Efficacy and analgesic use during the therapy of iatrogenic pneumothorax using Pleuralvent™ and Chest Tube (ASPIRATE): A randomised controlled trial protocol - Sova, Milan; Poruba, Martin; Genzor, Samuel; Jakubec, Petr; Zatloukal, Jaromir; Kolek, Vitezslav; Urbanek, Karel; Vasakova, Martina; Stehlik, Ludek; Zackova, Pavla; Asswad, Amjad Ghazal (Biomedical papers, 2020)
Background: Iatrogenic pneumothorax is a common complication of various diagnostic and therapeutic procedures such as transbronchial lung biopsies. The classical mode of treatment is chest tube insertion. Pneumothorax devices are now available on the market but there is a dearth of data on their efficacy to treat iatrogenic pneumothorax. It is important to provide such data as the pathophysiology of iatrogenic pneumothorax is different in comparison with spontaneous pneumothorax for which some data is available. Methods: This is a randomized, non-blinded, actively controlled trial of effectivity of iatrogenic pneumothorax treatment using the Pleuralvent™ device and chest tube insertion (16F). The secondary aim is to compare the overall pain level and the need for analgesic treatment in both treatment arms. We are planning to enrol 126 patients (63 in each treatment arm). Discussion: Preliminary results showed similar effectivity of the Pleuralvent™ system compared to large bore chest tube insertion. This randomized clinical trial should confirm these results and prove that the Pleuralvent™ system is an effective way of treatment of patients with iatrogenic pneumothorax. If Pleuralvent™ proves to have the same level of efficacy, it may become the standard of care of patients with iatrogenic pneumothorax. Trial registration: ClinicalTrials.gov Identifier: NCT03700554
Keywords: iatrogenic pneumothorax; Pleuralvent™; chest tube